Economic Growth and Stimulating Private Business Investment in Infrastructure by Assessing Its Need - Palei, Tatiana; Gurianova, Elina; Mechtcheriakova, Svetlana; Safiullin, Marat (International Journal of Criminology and Sociology, 2022)
Global statistics indicate increasing in private investors’ activity. Instead of the debate about the growing infrastructure needs and adequacy of funding to meet, the more urgent is the search for more effective mechanisms to attract investment in infrastructure assets. The chief objective of the study is to analyze the demand for infrastructure services to ensure the activities of organizations forming the priority clusters in the region, made for orientation on the existing industry need in the infrastructure support plans formation, concerning the construction financing of transport and other Infrastructure on a parity basis for economic growth. It is determined that the quality of transport connections play a vital role. It was established, that in all studied clusters, there is a tendency to increase transport services demand. Given the results, the petrochemical cluster enterprisestrochemical cluster is ready to finance transport infrastructure from the profits (perhaps on a matching base state) to remove the constraints of its industrial growth. For marginal assessment of investments into the development of a transport complex efficiency, the regression model "investments - profit" is received. It is suggested that with the growth of the industry, its profit is increasing at a rapid pace, each additional ruble of investment brings higher returns.